Triazole bridges as versatile linkers in electron donor-acceptor conjugates - De Miguel Rojas, Gustavo; Wielopolski, Mateusz; Schuster, David I.; Fazio, Michael A.; Lee, Olivia P.; Haley, Christopher K.; Ortiz, Angy L.; Echegoyen, Luis; Clark, Timothy; Guldi, Dirk Michael (Journal of the American Chemical Society, 2011)
Aromatic triazoles have been frequently used as π-conjugated linkers in intramolecular electron transfer processes. To gain a deeper understanding of the electron-mediating function of triazoles, we have synthesized a family of new triazole-based electron donor-acceptor conjugates. We have connected zinc(II)porphyrins and fullerenes through a central triazole moiety-(ZnP-Tri-C )-each with a single change in their connection through the linker. An extensive photophysical and computational investigation reveals that the electron transfer dynamics-charge separation and charge recombination-in the different ZnP-Tri-C conjugates reflect a significant influence of the connectivity at the triazole linker. Except for the m4m-ZnP-Tri-C 17, the conjugates exhibit through-bond photoinduced electron transfer with varying rate constants. Since the through-bond distance is nearly the same for all the synthesized ZnP-Tri-C conjugates, the variation in charge separation and charge recombination dynamics is mainly associated with the electronic properties of the conjugates, including orbital energies, electron affinity, and the energies of the excited states. The changes of the electronic couplings are, in turn, a consequence of the different connectivity patterns at the triazole moieties. © 2011 American Chemical Society.